Fadrozole-mediated sex reversal in the embryonic chicken gonad involves a PAX2 positive undifferentiated supporting cell state - Estermann, Martin A.; Smith, Craig A. (Frontiers in Cell and Developmental Biology, 2022)
Gonadal sex differentiation among vertebrates involves divergent fates of a common group of progenitor cells present in both presumptive ovaries and testes. The first cell type to differentiate gives rise to pre-Sertoli cells in the testis, and pre-follicular cells in the ovary. These cells derive from a common lineage of so-called “supporting cells”. In birds and other egg-laying vertebrates, locally synthesised estrogen has a central role in ovarian development and influences the fate of these supporting cells. Manipulation of estrogen levels during embryonic development induces gonadal sex reversal, providing an experimental setting to evaluate the process of gonadal sex differentiation. Recently, we identified PAX2 as a novel marker of the undifferentiated supporting cell lineage in the chicken embryo, expressed in both sexes prior to overt gonadal sex differentiation. PAX2 expression is downregulated at the onset of gonadal sex differentiation in both males and females. The analysis of this undifferentiated supporting cell marker, together with Sertoli (male) and pre-granulosa (female) will enhance our understanding of supporting cell differentiation. Here we characterized the supporting cells differentiation process and identified undifferentiated supporting cells in estrogen-mediated sex reversal experiments. Female embryos treated with the aromatase inhibitor fadrozole developed into ovotestis, containing pre-granulosa cells, Sertoli cells and PAX2 positive undifferentiated supporting cells. In contrast, male embryos treated with 17β-estradiol showed no PAX2+ undifferentiated gonadal supporting cells. Fadrozole time-course as well as multiple dose analysis suggests that supporting cell transdifferentiation involves a dedifferentiation event into a PAX2+ undifferentiated supporting cell state, followed by a redifferentiation towards the opposite sex lineage.